LEGAL ENFORCEMENT OF HEALTH PROTOCOL VIOLATION IN COVID-19 PANDEMIC - Nurul Alfiyani Hidayah; Mulyono Mulyono; Damrah Mamang (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2022)
The spread of the COVID-19 virus that has hit Indonesia at this time has had a wide impact on the joints of the life of the nation and state. Efforts to prevent and control the spread of the COVID-19 virus to be more effective have legal consequences, namely by implementing a criminal policy regarding limiting crowds with the threat of sanctions in the form of criminal sanctions, social sanctions and administrative sanctions. This study uses a normative juridical research method and is descriptive analytical. The regulation of criminal sanctions against perpetrators of violations of the health protocol, refers to Article 10 of the Criminal Code which consists of basic and additional penalties. The form of civil law sanctions can be in the form of obligations followed by the creation of new legal conditions. Social sanctions are types of sanctions outside the Criminal Code such as administrative sanctions, law enforcement against violations of health protocols as well as the criminal justice system. Such as the investigation and investigation stage, the prosecution stage, the examination stage in court and the decision implementation stage. One of the violations of health protocols that caused a crowd, which refers to the case that ensnared the Deputy Chairperson of the Tegal City DPRD Wasmad Edi Susilo, was sentenced by the Panel of Judges to imprisonment for 6 (six) months and a fine of Rp. 50,000,000.00,- (fifty million rupiah) provided that if the fine is not paid, it will be replaced with imprisonment for 3 (three) months. The results of this study indicate that both the Criminal Code and the special law on health quarantine are used as the basis for punishment for violators of health protocols. The criminal sanctions imposed by the government on perpetrators of violating health protocols are expected to be significant in dealing with Covid-19, of course, by considering the principle of proportionality and based on the goal of realizing justice.